1995
DOI: 10.1021/bi00002a011
|View full text |Cite
|
Sign up to set email alerts
|

Stability Studies on Maize Leaf Phosphoenolpyruvate Carboxylase: The Effect of Salts

Abstract: The solution stability of phosphoenolpyruvate carboxylase (PEPC) has been determined in the presence of various salts by temperature-accelerated enzyme inactivation and also by using high-performance size-exclusion chromatography. Kosmotropic (water structuring) anions in the Hofmeister series (HPO(4)2-, citrate3-, SO(4)2-, F-, OAc-) and glutamate stabilized the enzyme most effectively, while Cl- (a borderline Hofmeister anion) and Br- (a chaotropic anion) were destabilizing. The effects of the cations on PEPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…The activation parameters, in the presence of sodium phosphate, NaCl and (NH 4 + ) 2 SO 4 , point out the role played by ionic and hydrophobic interactions in the stabilization process of OCT and closely follow the Hofmeister series of anions (phosphate > SO 4 = > Cl − ). A similar trend in stabilization process has been noted by Damodoran [48] and Jensen et al [49]. The effects of ornithine could be due to conformational changes (as it can be seen by CD spectrum).…”
Section: Discussionsupporting
confidence: 83%
“…The activation parameters, in the presence of sodium phosphate, NaCl and (NH 4 + ) 2 SO 4 , point out the role played by ionic and hydrophobic interactions in the stabilization process of OCT and closely follow the Hofmeister series of anions (phosphate > SO 4 = > Cl − ). A similar trend in stabilization process has been noted by Damodoran [48] and Jensen et al [49]. The effects of ornithine could be due to conformational changes (as it can be seen by CD spectrum).…”
Section: Discussionsupporting
confidence: 83%
“…It is known to be a compatible solute (27,28). It enhances protein-nucleic acid interaction and stabilizes proteins from temperature inactivation (12,29). Several osmolytes play another important role in some organisms; that is, they counteract the effect of urea on protein structure.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins have been known to have specific ion binding sites Pace & Grimsley, 1988!. Some ions bind to proteins at very low concentrations and affect their stability~Makhatadze et al, 1998!, while other salts affect the stability in a general manner without having any specificity toward proteins~von Hippel & Schleich, 1969;Busby et al, 1981;Arakawa et al, 1990b;Bonnette et al, 1994;Jensen et al, 1995!. The differential stability provided by salts of different combinations indicates the contribution of both the cations and anions for providing stability to the protein to an extent depending on their position in the Hofmeister series~Hofmeister, 1888; Baldwin, 1996!. In salt systems the effect of an individual ion has been found to be essentially additive~Arakawa & Timasheff, 1991!. Salts that do not have specific binding to proteins increase their thermal stability essentially through their effect on water structure manifested by an increase in its surface tension~Sinanoglu & Abdulnur, 1965;Lin & Timasheff, 1996!. It is suggested that protein stability and solubility are linked to this phenomenon.…”
mentioning
confidence: 99%